Identifying vaccination deserts: The availability and distribution of pharmacists with authorization to administer injections in Ontario. (September 2022) - Houle, Sherilyn K.D.; Timony, Patrick; Waite, Nancy M.; Gauthier, Alain
Introduction: Pharmacist-administered immunizations have been associated with improved vaccination rates; however, little is known about whether areas with little to no access to this service ("vaccination deserts") exist. The objective of this work is to determine the geographic availability of pharmacists with authorization to administer injections in the province of Ontario. Methods: Ontario College of Pharmacists registry data were used to identify patient care–providing pharmacists in community pharmacies and their ability to administer injections. Their number of hours worked was converted into full-time equivalents (FTEs), assuming 40 hours per week represents 1 FTE. Practice site(s) were mapped by postal code and presented by Public Health Unit (PHU) area. Communities within PHUs were further categorized as urban or rural and northern or southern, with ratios of FTEs per 1000 population calculated for both injection-trained and non-injection-trained pharmacists. Results: In total, 74.6% of Ontario's practising community pharmacists are authorized to provide injections. Northern PHUs had slightly better access to pharmacist injectors (0.61 FTEs/1000 overall vs 0.56/1000 in the south), while rural communities had lower availability (0.41 FTEs/1000) than urban communities (0.58 FTEs/1000). PHUs with greater population size and density had greater availability of pharmacist immunizers, while PHUs with greater land area were more likely to not have any immunizing pharmacists present ( p < 0.001 for all). Discussion: As pharmacists increasingly become preferred vaccination providers, awareness of disparities related to access to pharmacy-based immunizations and collaboration with public health and primary care providers to address them (e.g., through mobile vaccination clinics) will be required to ensure equitable access. Can Pharm J (Ott) 2022;155:xx-xx.